2006
DOI: 10.1074/jbc.m509201200
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin and Mutant SOD1 Form Aggregate Structures with Distinct Molecular Properties in Human Cells

Abstract: Expression of many proteins associated with neurodegenerative disease results in the appearance of misfolded species that readily adopt alternate folded states. In vivo, these appear as punctated subcellular structures typically referred to as aggregates or inclusion bodies. Whereas groupings of these distinct proteins into a common morphological class have been useful conceptually, there is some suggestion that aggregates are not homogeneous and can exhibit a range of biological properties. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
117
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 60 publications
10
117
0
Order By: Relevance
“…Aggregate size and morphology was likewise unaltered (Fig. 2b) similar to what has been reported previously 20,21 . Consistent with the visual increase in aggregate-containing cell numbers was an increase in htt protein detected by the filter trap assay for 7.5-fold (Fig.…”
supporting
confidence: 88%
“…Aggregate size and morphology was likewise unaltered (Fig. 2b) similar to what has been reported previously 20,21 . Consistent with the visual increase in aggregate-containing cell numbers was an increase in htt protein detected by the filter trap assay for 7.5-fold (Fig.…”
supporting
confidence: 88%
“…Other experiments have suggested that familial ALS (fALS)-associated mutant SOD1 is most toxic when localized to an IB (8). It has also been shown that toxic SOD1 IBs are more dynamic than Htt inclusions, and interact with quality control machinery (19,23). The differences between these IBs may represent differences in function (degradation vs. sequestration).…”
Section: Resultsmentioning
confidence: 99%
“…Given that yeast studies of JUNQ and IPOD (15) as well as several studies in mammalian cells (19) have observed aggregate inclusions with different properties, we set out to coexpress different types of aggregation-prone proteins to track their localization and effect on cell viability. By imaging live cells expressing fluorescently tagged proteins, we observed that in human cells, as in yeast, normal misfolded proteins (VHL and Ubc9 ts ) localize to JUNQ-like compartments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HSPB6, which only effectively suppresses shorter polyQs [1,107], also plays a role in modulating autophagy [108]. By contrast, HSPB7 does not change the rate of proteasomal degradation and does not increases the autophagic flux; rather, it appears to prevent early aggregates from nucleating into inclusions with sizes that are too large to be handled by the autophagic machinery, probably by marking these early seeds, which enables their shuttling into the autophagosomes [1,57,109,110]. This HSPB7 action thus does not rely on the speed of seed formation but rather on the rate at which these seeds grow (and thus is less dependent on the size of the expansion).…”
Section: The Anti-aggregation Power Of Hspbs Depends On Several Factorsmentioning
confidence: 99%
“…Indeed, the effects of HSPB members on different aggregation-causing mutants seem to differ widely (table 1). It has been shown that, while polyQ proteins form aggregates with a core that is inaccessible to nascent proteins, mutated SOD1 (G85R/G93A), associated with ALS, forms a porous aggregate, through which nascent proteins can diffuse [110]. As stated above, we have already shown that overexpression of HSPB8 efficiently prevented the aggregation and facilitated the autophagy-mediated degradation of mutated SOD1 and of various mutated forms of TDP43, which is associated with both ALS and FTD [43] (figure 3a).…”
Section: The Anti-aggregation Power Of Hspbs Depends On Several Factorsmentioning
confidence: 99%